2017
DOI: 10.1111/pan.13066
|View full text |Cite
|
Sign up to set email alerts
|

A case‐controlled comparison of postoperative analgesic dosing between girls with Rett syndrome and girls with and without developmental disability undergoing spinal fusion surgery

Abstract: Background Rett syndrome (RTT) is associated with severe motor and communicative impairment making optimal postoperative pain management a challenge. There are case-reports documenting reduced postoperative analgesic requirement in RTT. Aim The goal of this preliminary investigation was to compare postoperative analgesic management among a sample of girls with RTT compared to girls with and without developmental disability undergoing spinal fusion surgery. Method The medical records of 8 girls with Rett sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Venipuncture is a distressing procedure in children with SNI compared to healthy peers ( 31 , 32 ), and these data highlighted the need for pain management strategies in this population, such as the mandatory use of topical anaesthesia. Likewise, the literature highlights the risk of undertreatment of pain after surgery in children with SNI ( 9 , 10 ). This series’ high number of surgical procedures reminds paediatricians of the need for careful pain evaluation and treatment after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venipuncture is a distressing procedure in children with SNI compared to healthy peers ( 31 , 32 ), and these data highlighted the need for pain management strategies in this population, such as the mandatory use of topical anaesthesia. Likewise, the literature highlights the risk of undertreatment of pain after surgery in children with SNI ( 9 , 10 ). This series’ high number of surgical procedures reminds paediatricians of the need for careful pain evaluation and treatment after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies offered hints and lists of features that indicate pain in non-verbal children and highlighted possible expressions of pain ( 1 ). This assessment is critical in acute pain episodes and in the context of procedural or post-operative pain where there is still a higher risk of undertreatment ( 9 , 10 ). Gross Motor Function Classification System (GMFCS) is a pragmatic system that further delineates the severity of motor and functional limitations mostly of children with cerebral palsy, but it is also broadly used in other patients with SNI and CMC ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surgery should not be delayed until skeletal maturity has been achieved. Barney and colleagues suggested the need for RTT-specific post-operative pain management [22]. The authors reported that, after spinal fusion, patients with RTT received fewer total doses of opioids compared to girls with cerebral palsy and idiopathic scoliosis.…”
Section: Introductionmentioning
confidence: 99%